Addressing the main challenges of energy security in the twenty-first century – Contributions of the conferences on Sustainable Development of Energy, Water and Environment Systems. (15th November 2016) - Markovska, Natasa; Duić, Neven; Mathiesen, Brian Vad; Guzović, Zvonimir; Piacentino, Antonio; Schlör, Holger; Lund, Henrik
Abstract: Climate change and fossil fuel reserve depletion both pose challenges for energy security and for wellbeing in general. The top ten among them include: Decarbonising the world economy; Enhancing the energy efficiency and energy savings in buildings; Advancing the energy technologies; Moving towards energy systems based on variable renewables; Electrifying the transport and some industrial processes; Liberalizing and extending the energy markets; Integrating energy sectors to Smart Energy Systems; Making the cities and communities smart; Diversifying the energy sources; and Building more biorefineries. Presenting the contributions of selected conference papers published in the special issues of leading scientific journals (including all the papers from the current Energy special issue), this review demonstrates the capacity of the Conferences on Sustainable Development of Energy, Water and Environment Systems for generation of knowledge which could serve as the centrepiece of a pertinent response to those challenges. Highlights: Top ten challenges of energy security in the twenty-first century identified. Selected SDEWES contributions analysed against the identified challenges. The role of SDEWES as knowledge generator towards addressing the identified challenges credibly demonstrated.